A produção residencial por empresas privadas: sua influência no território urbano de São José do Rio Preto/ SP de 2000 a 2015 - Lisbôa, Cristian Roberto Nazareth (2019)
The present work shows a study regarding the private residential real estate production by companies and its influence in São José do Rio Preto-SP urban morphology. The research is a product of primary data gathering, acquired with the county, and its analysis. Such data consists in licensing derived from certificates of occupancy issued to company made residential buildings from 2000 to 2015. The research discusses how the growing implantation of private residential real estate enterprises, aimed to diverse social strata, has provoked changes into the housing provision structure, both new and consolidate areas value increase, the growth of urban voids and the city’s spreading. The work shows that there has been an expansion-retraction cycle and that the expansion apex occurred in 2012, but that there has been successive retractions of the productive volume in the following years. In what regards the urban mesh, initially this production spatialization happened foremost at the south and east county areas. Although, later, it converged into the north area creating considerable impacts in that area’s real estate excessive price increase. During this process, it was also verified the open capital companies important participation in the housing provision structure analyzed, as well as a forged partnership between the county public power, the incorporation capital and the real estate entrepreneurs.